2019
DOI: 10.1590/0034-761220180125x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the project management office on scientific research

Abstract: Resumo O objetivo deste artigo é demonstrar que o escritório de gestão de projetos, uma unidade organizacional reconhecida pelo guia Project Management Body of Knowledge (PMBOK®), pode apoiar o cientista na gestão de projetos de pesquisa, de modo que ele se dedique a outras atividades. Para testar a hipótese, detalha-se o marco teórico e a coleta de dados de projetos financiados pela Fundação de Apoio à Pesquisa no Estado de São Paulo (Fapesp) e executados na Faculdade de Medicina de Ribeirão Preto da Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the case of scientific research management, the idea is to save the scientist the workload necessary to manage these increasingly complex, high-value projects with teams from different entities, so that he can dedicate himself to other activities aimed at science (increasingly organised and competitive) and student guidance (Junqueira & Passador, 2019).…”
Section: Research Ecosystemmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of scientific research management, the idea is to save the scientist the workload necessary to manage these increasingly complex, high-value projects with teams from different entities, so that he can dedicate himself to other activities aimed at science (increasingly organised and competitive) and student guidance (Junqueira & Passador, 2019).…”
Section: Research Ecosystemmentioning
confidence: 99%
“…Additionally, another study conducted between 2009 and 2015 on research projects from FMRP-USP evaluated quantitatively time, cost and quality variables and concluded that CGP helped projects meet the expected deadline, helped also the projects have their accountability approved according to the expected requirements and quality without rework (Junqueira & Passador, 2019).…”
Section: Research Ecosystemmentioning
confidence: 99%
“…Conducting a large-scale study on CSF, Pinto and Slevin (1987) identified ten key CSFs that greatly impacted project success. Subsequently, many researchers stuck to this line of factors for various types of projects and began to argue that planning is considered in project management as one of the main success factors for a project (Dvir, There are substantiated conclusions about the role of the project management methodology (PMM) as a factor in the success of projects (Junqueira & Passador, 2019), which should be taken into account when developing a project plan, in our opinion, is a subjective factor.…”
Section: Literature Reviewmentioning
confidence: 99%